1994
DOI: 10.1093/oxfordjournals.eurheartj.a060428
|View full text |Cite
|
Sign up to set email alerts
|

Transthoracic echo/Doppler in the identification of patients with chronic non-valvular atrial fibrillation at risk for thromboembolic events

Abstract: transthoracic echo/Doppler aids in the prediction of the presence of left atrial spontaneous echo contrast and the identification of patients with non-valvular atrial fibrillation with increased cardioembolic risk, thus avoiding transoesophageal echocardiography.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…These parameters were quantified in several consecutive measurements in diastole for an average R-R interval as measured by continuous monitoring during echocardiography. This technique is in line with former study protocols (10).…”
Section: Study Populationsupporting
confidence: 80%
“…These parameters were quantified in several consecutive measurements in diastole for an average R-R interval as measured by continuous monitoring during echocardiography. This technique is in line with former study protocols (10).…”
Section: Study Populationsupporting
confidence: 80%
“…[213][214][215][216][217][218] Specifically, SEC, or "smoke," a swirling haze of variable density, may be detected by transthoracic or transesophageal echocardiographic imaging of the cardiac chambers and great vessels under low-flow conditions. 219 This phenomenon relates to fibrinogenmediated erythrocyte aggregation 220 and is not resolved by anticoagulation.…”
Section: Pathophysiology Of Thrombus Formationmentioning
confidence: 99%
“…In addition, the diastolic augmentation of LAA outflow was also higher in patients with a good left ventricular ejection fraction. Pop et al [24] also demonstrated that patients with a larger transmitral inflow velocity-time integral had less incidence of left atrial SEC. As the LAA flow velocity is influenced by the loading condition of the left atrium [25], the increased left atrial pressure secondary to the increased left ventricular end-diastolic pressure might also play a role in the attenuation of LAA outflow in the patients with impaired left ventricular function.…”
Section: Effect O F Left Ventricular Function On Laa Outflowmentioning
confidence: 95%